The Levant as a code of deterritorialization for Amin Maalouf - Saima Bashir; Sohail Ahmad Saeed (Cogent Arts & Humanities, 2024)
The article makes an exploration of three motifs in the context of Lebanese-French Arab migrant writer Amin Maalouf’s fictional text Ports of Call (2001) by applying the theoretical framework of deterritorialization and reterritorialization as presented by the French theorists Gilles Deleuze and Felix Guattari and expanded by the Indian-American theorist Arjun Appadurai. As suggested by the four key words of the writer’s introduction–namely ‘Lebanese’, ‘French’, ‘Arab’ and ‘migrant’–the three motifs being de-composed into their basic components are identity, especially the migrant identity, the Levant as a symbol of the migrant’s lost home and deterritorialization/reterritorialization in the context of globalization. Migrants are deterritorialized and departure from long-established origins causes a disruption in the conventional notions of ‘home’ and ‘identity’ turning them into something fluid rather than fixed. This leads to a revision of the postcolonial postulation which makes migrancy a locus for the reworking of nation’s primacy as a referent in the construction of identity. The intricate nature of relation between political and personal experiences highlights the tangling of ideological stances on nation and nationalism in the cultural production taking place at the site of migration.